2013
DOI: 10.1089/pho.2013.3549
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nd:YAG Laser Pulse Energy on Mercury Vapor Release from the Dental Amalgam

Abstract: The amount of mercury vapor significantly increased with an increase in the pulse energy of the laser beam, and was significantly higher than the standard mercury vapor concentration with 250 mJ pulse energy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Akgun et al, reported that MRI cannot change the microleakage of bonded or nonbonded amalgam fillings [ 45 ]. Moreover, laser beams (Nd:YAG) with the pulse energies of 50, 150, and 250 mJ increased the mercury vapor release, that was dependent on the Nd:YAG laser pulse energy [ 30 ]. However, Pioch et al, showed that CO 2 laser, no signs of amalgam ablation or mercury vapor release were observed [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Akgun et al, reported that MRI cannot change the microleakage of bonded or nonbonded amalgam fillings [ 45 ]. Moreover, laser beams (Nd:YAG) with the pulse energies of 50, 150, and 250 mJ increased the mercury vapor release, that was dependent on the Nd:YAG laser pulse energy [ 30 ]. However, Pioch et al, showed that CO 2 laser, no signs of amalgam ablation or mercury vapor release were observed [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that magnetic resonance imaging (MRI) [ 28 ], chewing and brushing in an artificial mouth [ 29 ], Nd:YAG laser pulse energy [ 30 ], radiofrequency radiation sources including Wi-Fi routers, smartphones, light-curing tools [ 31 ] and also X-rays [ 32 ] might change the rate of evaporation of mercury from amalgam fillings. Iranian scientists firstly addressed this issue in 2008 [ 33 ] but more than 10 years later, it became viral worldwide [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation